LIGHT/TNFSF14 Promotes Osteolytic Bone Metastases in Non‐small Cell Lung Cancer Patients. (7th January 2020) - Brunetti, Giacomina; Belisario, Dimas C; Bortolotti, Sara; Storlino, Giuseppina; Colaianni, Graziana; Faienza, Maria F; Sanesi, Lorenzo; Alliod, Valentina; Buffoni, Lucio; Centini, Elisa; Voena, Claudia; Pulito, Roberta; et al.
ABSTRACT: Tumor necrosis factor superfamily member 14 ( TNFSF14 ), LIGHT, is a component of the cytokine network that regulates innate and adaptive immune responses, which promote homeostasis of lymphoid organs, liver, and bone. Metastatic tumors often disrupt the tissue microenvironment, thus altering the homeostasis of the invaded organ; however, the underlying mechanisms required further studies. We investigated the role of LIGHT in osteolytic bone disease induced by metastatic non‐small cell lung cancer (NSCLC). Patients diagnosed with NSCLC bone metastasis show significantly higher levels of LIGHT expressed in monocytes compared with non‐bone metastatic tumors and healthy controls. Serum LIGHT levels were also higher in patients with bone metastases than in controls, suggesting a role for LIGHT in stimulating osteoclast precursors. In bone metastatic patients, we also detected increased RNA expression and serum RANKL levels, thus by adding anti‐LIGHT or RANK–fragment crystallizable region (RANK‐Fc) in PBMC cultures, a significant inhibition of osteoclastogenesis was observed. To model this observation in mice, we used the mouse lung cancer cell line LLC‐1. After intratibial implantation, wild‐type mice showed an increased number of osteoclasts but reduced numbers of osteoblasts and decreased osteoid formation. In contrast, Tnfsf14 −/− mice showed no significant bone loss or other changes in bone homeostasis associated with this model. These data indicate LIGHT is a key control mechanism for regulating bone homeostasis during metastatic invasion. Thus, LIGHT may be a novel therapeutic target in osteolytic bone metastases. © 2019 American Society for Bone and Mineral Research.